Probleme obshchei vynoslivosti v sisteme podgotovki sportsmenov (terminologiya, kriterii, reshaemye zadachi) - Suslov, F. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to discuss some problems of the endurance in the system of athletes training in the aspect of definitions and concepts. The definitions of the general and the special endurance are analysed. The author considers that the concrete interpretation of the endurance in the contemporary system of athletes' training is limited by the special endurance. The special endurance has some leading components for every sports discipline. The author offers his conception of the general endurance as an element of the general physical performing.